Viscoelastic multi-dimensional self-resetting coupling beam damper and shock resistance toughness improving method thereof - ZHU LIHUA; XU ZHAODONG; GAO WANG; DONG YAORONG; SHI QINGXUAN (2023)
The invention discloses a viscoelastic multi-dimensional self-resetting coupling beam damper and an anti-seismic toughness improving method thereof. The damper is composed of a main body steel plate part, an energy dissipation unit, a self-resetting unit and a load transmission component. The energy dissipation unit is divided into a vertical shear energy dissipation unit and a rotary shear energy dissipation unit, and the energy dissipation main materials of the vertical shear energy dissipation unit and the rotary shear energy dissipation unit are both viscoelastic materials; the self-resetting unit is divided into a self-adaptive self-resetting unit, a vertical stretching self-resetting unit and a transverse stretching self-resetting unit; the load transmission component comprises a lever dowel bar and rotating steel cylinders with different diameters. When the main body steel plate is subjected to a structural load, the load transmission component transmits a dynamic response of the structure to the energ